DOENÇA DE ALZHEIMER: ESTRATÉGIAS DE CUIDADOS QUE PODEM AUXILIAR NAS DIFICULDADES VIVENCIADAS PELOS FAMILIARES (REMUNOM, 2023)
Alzheimer's disease is characterized by neurodegenerative dementia or loss of cognitive functions such as memory, language, behavior, attention and orientation. We have the nurse and the family as the main actors in the improvement and better quality of life of the Elderly with Alzheimer's Disease. It is important to know that for a well-being in the life of an elderly person with AD, one must know how this disease works and how it affects the daily lives of everyone around them. Nurses in their role must know how to guide and create relevant strategic ways to know how to deal, together with their team and family, with the dysfunctions that this disease brings and the difficulties it shows in everyday life. The quality of life of the elderly is associated with the way they lead their daily lives and it is important that their care is calm and gradual, thus becoming something lighter for the elderly and their family. In view of the above, the research objective was to outline training strategies for family caregivers of patients with Alzheimer's. To achieve this, it was decided to use a qualitative methodology, which aims to carry out a descriptive research, through a bibliographical review. In the end, it was considered extremely important that family members have support and contact with the health strategy nurse and know how to deal with the elderly person who has Alzheimer's disease, knowing how to solve difficulties and challenges and considering how important it is to have a support network and knowledge about the daily care that should be given to this elderly person, and it is also important for the caregiver to promote self-care to avoid possible psychological damage.